Kesantunan Berbahasa dalam Dakwah Multikultural - Herniti, Ening; Budiman, Arif; Kusumawati, Aning Ayu (Adabiyyāt: Jurnal Bahasa dan Sastra, 2016)
Politeness is reflected in the use of verbal sign. Politeness is also found in multicultural dawah. Multicultural dawah means to summon or invite people of different cultural backgrounds to learn more about Islam, but its deliverance does not offend, hurt, obtrude, or impose its audiences. This paper describes the politeness indicators and supporting values of politeness in multicultural dakwah. The data were taken form youtube, documented by data transcription, and then analyzed by using theory of politeness. The conclusion of this study shows that these multicultural dawah obey the politeness indicators such as angon rasa, adu rasa, empan papan, humility, respect, tepa selira, diction of "sorry", "thank you', and greeting "Sir/Madam". However, in these multicultural dakwah, there were also found the disobediences of the politeness indicators. This disobediences are due to the usage of inappropriate dictions. The supporting values of politeness include humility, empan papan,keep the feeling and attitude of introspection.